The potential role of telocytes in Tissue Engineering and Regenerative Medicine - Boos, Anja; Weigand, Annika; Brodbeck, Rebekka; Beier, Justus; Arkudas, Andreas; Horch, Raymund E. (Seminars in Cell & Developmental Biology, 2016)
Research and ideas for potential applications in the field of Tissue Engineering (TE) and Regenerative Medicine (RM) have been constantly increasing over recent years, basically driven by the fundamental human dream of repairing and regenerating lost tissue and organ functions. The basic idea of TE is to combine cells with putative stem cell properties with extracellular matrix components, growth factors and supporting matrices to achieve independently growing tissue. As a side effect, in the past years, more insights have been gained into cell-cell interaction and how to manipulate cell behavior. However, to date the ideal cell source has still to be found. Apart from commonly known various stem cell sources, telocytes (TC) have recently attracted increasing attention because they might play a potential role for TE and RM. It becomes increasingly evident that TC provide a regenerative potential and act in cellular communication through their network-forming telopodes. While TE in vitro experiments can be the first step, the key for elucidating their regenerative role will be the investigation of the interaction of TC with the surrounding tissue. For later clinical applications further steps have to include an upscaling process of vascularization of engineered tissue. Arteriovenous loop models to vascularize such constructs provide an ideal platform for preclinical testing of future therapeutic concepts in RM. The following review article should give an overview of what is known so far about the potential role of TC in TE and RM.
EVALuna2:15617